Mucocele: An unusual presentation of the minor salivary gland lesion - B Senthilkumar; M Nazargi Mahabob (Wolters Kluwer Medknow Publications, 2012)
A mucocele is a benign, mucus-containing cystic lesion of the minor salivary gland. This type of lesion is most commonly referred to as mucocele. The more common is a mucus extravasation cyst; the other is a mucus retention cyst. Other three clinical variants are: Superficial mucocele that is located directly under the mucosa, classic variant located in the upper submucosa, and deep mucocele located in the lower cornium. Mucocele occurs either due to rupture of salivary gland duct or by blockade of salivary gland duct. The common site of occurrence of mucocele is lower lip followed by tongue, floor of mouth (ranula), and the buccal mucosa.